Differentially Expressed miRNAs in Acute Wound Healing of the Skin: A Pilot Study. Issue 7 (February 2015) - Li, Ping; He, Quanyong; Luo, Chengqun; Qian, Liyuan
Abstract : Abstract: The aim of the present study was to compare expression of microRNAs (miRNAs) from scar and normal skin areas in patients who suffered acute injuries in the skin. A total of 9 patients with acute injuries in the skin who received surgical treatment from December 2012 to March 2013 were included in this pilot study. Specimens from the hypertrophic scar and normal skin areas were obtained from the same patient during surgery. To screen for differentially expressed miRNAs, we applied 3 statistical methods, namely the traditional t test, the false discovery rate (FDR), and a novel sure independence screening procedure based on the distance correlation (DC-SIS). We examined the functional trends and metabolic and regulatory pathways for the target genes of the identified miRNAs, and explored interaction of these miRNAs in the implication of scar healing using Ingenuity Pathway Analysis. DC-SIS identified 18 differentially expressed miRNAs, 4 of which (miR-149, miR-203a, miR-222, miR-122) were also identified by FDR. The target genes of the 4 miRNAs exhibit a variety of biological functions, and are involved in various pathways such as mitogen-activated protein kinase, Wnt signaling, and focal adhesion. We identified 1 network in which 14 out of the 18 differentially expressed miRNAs were involved. Many of the miRNAs in the network target genes were involved in cell proliferation and apoptosis. In this pilot study, we identified several miRNAs exhibiting differential expression in patients who suffered acute injuries in the skin. Further studies on these miRNAs are needed to validate our findings and explore their roles in the wound healing process of the skin.